KAJIAN RESIDU BIOCHAR SEKAM PADI, KAYU DAN TEMPURUNG KELAPA TERHADAP KETERSEDIAAN AIR PADA TANAH LEMPUNG BERLIAT - Anita Nur Khoiriyah; Cahyo Prayogo; W Widianto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2016)
The water content of the soil in Jatikerto is 32,02%. As it is supported by clayey loam soil texture, the soil is able to absorb more water, but the water in the soil cannot necessarily be available to the plants. One effort to maintain the availability of ground water can be done with the soil amendments materials such as biochar. This study used three types of biochar, i.e. rice husk, coconut shell, and wood with each contained three doses (15, 30 and 45 t ha-1). This study used ten treatments with two factors consisted of types and doses of biochar. Soil sampling was conducted at 2 points on the array and on an array, and each point was conducted on soil depth of 0-20 cm and 20-40 cm. The variables measured were soil texture, soil bulk density, soil porosity, pore space distribution, pore fast drainage, pore slow drainage and pores water available. The results indicated that treatments of types and doses of biochar did not change the texture of the soil. The highest soil bulk density contained in biochar types of wood biochar dose of 30 t ha-1 (1,20 g cm-3), while for soil particle density was not significantly influenced by the biochar treatments. The average value of the highest porosity was measured on the type of wood biochar dose 15 t ha-1 (47,54% vol). The highest pore fast drainage contained in biochar types of coconut shell biochar dose of 30 t ha-1 (20,80% vol), while for the highest available pore water was on the type of coconut shell biochar dose 45 t ha-1(21,55% vol). The highest pore slow drainage was on the type of wood biochar dose 30 t ha-1 (29,03% vol).